Development of Learning Design for English Courses Based on Learning Outcomes: Strategies of the Department of Christian Leadership in Achieving Graduate Science and Profession - Robert Juni Tua Sitio; Boho Parulian Pardede; Chandra Siagian; Kimson Sinaga (Al Hikmah: Journal of Education, 2023)
This research aims to develop a learning design for English courses based on learning outcomes in the method and learning materials in the curriculum to support the scientific and professional achievements of graduates of the Christian Leadership Department. This research method is descriptive qualitative with a survey method of 3 lecturers and 12 students as respondents. The results showed that the results of the development of the learning design for the English course in the Christian Leadership Department curriculum obtained an average score of 4.1 â‰¥Hâ‰¥3 in the high category and then converted into a percentage gain of 82% in the very good category. This study recommends improvement in students' writing skills which must be trained and continuously developed in writing prayers, reflections or short sermons in English.